Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan pada PT Pratama Rindo Raya Jakarta Utara - Desi Pitasari; Bilgah Bilgah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Performance is a description of a result that can be measured by the effectiveness and efficiency of work carried out by human resources in realizing the targets, goals, vision and mission that are realized through a company's planning strategy. This research aims to determine and analyze the influence of the environment and motivation on employee performance at PT Pratama Rindo Raya. This research uses a quantitative statistical approach method. The sampling technique used was saturated sampling which had 38 respondents. Data collection techniques use observation through questionnaires. The results of this research show that the work environment (X1) has a significant effect with a value of 0.848 or 84.8%, which means that the work environment variable (X1) has a strong influence on employee performance (Y). Motivation (X2) has a significant effect with a value of 0.842 or 84.2%, which means that the motivation variable (X1) has a strong influence on employee performance (Y). The work environment (X1) and motivation (X2) simultaneously (together) have a significant influence on employee performance (Y) at PT Pratama Rindo Raya with a value of 90.4% and the remaining 9.6% is influenced by factors others that researchers are not careful about.